PENGEMBANGAN MEDIA PEMBELAJARAN MATA PELAJARAN FISIKA SMA BERBASIS KOMPUTER - Ahmad Arif Ma'sum (STKIP Melawi, 2014)
Abstract: This research aims to produce a proper Computer-based Instructional Media for dynamic electricity as a source of study for senior high school students. This study is a research and development study. Respondents of this research were the XI grade students of SMA Muhammadiyah 1 Yogyakarta. Of the 47 respondents, 6 students were treated in a one-by-one experiment, 12 students were treated in a small group evaluation, and 29 students were for the field try-out. The techniques of collecting data were observation and giving questionnaires. The instruments used in collecting the data were validation sheets for the media expert and content expert, observation sheets and questionnaires for the students. The data were analyzed by using the descriptive analysis. The result of the research shows the following. Development of computer-based learning media for Physics was conducted in several steps: needs analysis, product development, field experiment, and dissemination of the result. Based on the validation of the content expert the learning aspect is on the good category with a mean score of 3.65, and based on the result of validation of the media experts the appearance aspect falls in the very good category with a mean score of 4.63. The result of field research shows that humanistic aspect and content are in the very good category with a mean score of 4.28, and attractiveness aspect of the media falls in the very good category with a mean score 4.24. This evaluation shows that: (1) The produced computer-based learning media for Physics is feasible to be used as one of the sources of student learning. (2) The computer-based learning media for Physics is properly developed. (3) The computer-based learning media for Physics is effective to be used because it is able to improve the student performance. This is proven by the increase of the pre-test to post-test scores as much as 48.75%.Key Words: Computer-based Instructional Media for dynamic electricity, Physics, development studyAbstrak: Penelitian ini bertujuan untuk menghasilkan produk media pembelajaran listrik dinamis berbasis komputer yang layak sebagai sumber belajar untuk siswa SMA. Jenis penelitian ini adalah penelitian pengembangan. Responden penelitian adalah siswa SMA Muhammadiyah 1 Yogyakarta kelas XI. Responden dalam penelitian ini sebanyak 47 orang yang terdiri 6 orang siswa uji coba satu-satu, 12 orang siswa uji coba kelompok kecil, dan 29 orang siswa uji coba lapangan. Instrumen yang digunakan dalam pengumpulan data adalah lembar validasi untuk ahli media dan ahli materi, lembar observasi dan kuesioner untuk siswa SMA. Teknik pengumpulan data dengan cara observasi dan kuesioner. Data dianalisis dengan menggunakan analisis statistik deskriptif. Hasil penelitian menunjukkan bahwa pengembangan media pembelajaran mata pelajaran fisika berbasis komputer dikembangkan melalui beberapa tahap yaitu: analisis kebutuhan, pengembangan produk, uji lapangan, dan diseminasi. Berdasarkan hasil validasi ahli materi aspek pembelajaran masuk kategori baik (rerata 3,65), dan hasil validasi ahli media menunjukkan bahwa aspek tampilan media masuk kategori sangat baik (4,63). Hasil uji coba lapangan menunjukkan bahwa aspek humanistik dan materi masuk kategori sangat baik (rerata 4,28), dan aspek kemenarikan media masuk kategori sangat baik (rerata 4,24. Hasil penilaian ini menunjukkan bahwa: (1) produk pengembangan media pembelajaran mata pelajaran fisika berbasis komputer ditinjau dari kualitas materi layak digunakan sebagai sumber belajar. (2) Pengembangan media pembelajaran mata pelajaran fisika berbasis komputer ditinjau dari kualitas tampilan program layak dikembangkan. (3) Pengembangan media pembelajaran mata pelajaran fisika berbasis komputer efektif untuk digunakan karena mampu meningkatkan hasil belajar siswa. Terbukti dengan rata-rata prosentase kenaikan nilai pre-test ke post-test sebesar 48,75%.Kata Kunci: media pembelajaran listrik dinamis berbasis komputer, fisika, penelitian pengembangan